Combining ability and gene action for yield in indigenous accessions of Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Seed yield improvement in Indian mustard (Brassica juncea) needs the information about the nature of gene action and both type of combining ability involved in expression of various useful traits that are responsible for yield improvement. Combining ability analysis helps to identification of the suitable parents for hybrids development. Present study was conducted to determine combining ability of 23 genotypes (8 parents and 15 F1s) of Indian mustard. Line × tester analysis including 5 lines and 3 testers exhibited the operation of additive (fixable) and non-additive (non-fixable) gene actions with predominance of non-additive gene action in controlling yield components. Only one genotype, namely, IC317528 was identified the best general combiner possessing highly significant positive GCA (General Combing Ability) and IC335858 × IC571648, IC589669 × IC571655 were exhibit high SCA (Specific Combining Ability) effects for seed yield. Genotypes IC571655, IC589670, IC571683 were significant negatively for early flowering. Significant SCA effect for earliness, plant height, seed yield and other contributing characters in desirable direction were recorded in a series of hybrids.